Diseño y construcción de un dispositivo biosensor portátil de bajo costo usando tecnología IoT para la monitorización remota de signos vitales enfocado a pacientes que padecen enfermedades crónicas - Rivilla Armijos, Kleyner Antonio (2024)
This project involves designing and constructing a low-cost, portable biosensor device using IoT technology for the remote monitoring of vital signs in patients with chronic diseases, such as heart and lung conditions. The goal is to enhance medical follow-up and improve the quality of life for these patients by implementing a system that enables real-time monitoring outside of the hospital environment. The development of the prototype was conducted in four phases: research and information analysis, design, implementation, testing, and evaluation of the results. The findings demonstrated the device's ability to detect and transmit vital signs, including oxygen saturation (SpO2), heart rate, body temperature, ECG, and PPG signals, using MAX30102, AD8232, and LM35 sensors. Wi-Fi technology was employed to integrate with IoT platforms such as Firebase, facilitating data visualization and analysis and sending real-time alerts via WhatsApp. The analysis indicated that the device is useful for continuous monitoring, with a low average error rate compared to conventional medical devices. Keywords: Chronic diseases, monitoring, IoT, sensors, Wi-Fi, vital signs.